PENDEKATAN CONTEXTUAL TEACHING AND LEARNING TERHADAP HASIL BELAJAR DRIBBLE BOLA BASKET (STUDI PADA SMAK SANTO ALBERTUS MALANG) - GEROL FOEKH, RISTO (Jurnal Pendidikan Olahraga dan Kesehatan, 2014)
Abstract The use of learning approach which is appropriate with students need may solve problems in basketball dribbling. One of the approach is by using contextual teaching and learning  approach. Perhaps, by this approach students will be easy to learn basketball dribbling correctly.In this research, subject of the research is students grade eleven SMAK Santo Albertus Malang who has connection with  implementation of physic and exercise subjects. The pretest data is collected as follow: distance of chair from the start line until the first chair is 5 ft or 1.5 m; distance from chair to chair is 8 ft or 2.4 m; distance of overall filed is 45 ft or 13.7 m. Students stand on start line with ball in hand and wait instruction of start. Students start by dribbling and direct  their ball to the right side of chair and then dribbling in out when pass the chair and play the same thing back to start line.In relation with problem formula, aim and result of the research about contextual teaching and learning approaches  to learning outcomes of basketball dribbling, it can be concluded that from results of one sample test indicate  that H0 is rejected and Ha is accepted because ? t > t posttest t  17,098  df 15   signifikasi .000 Mean difference 12,23188 lower 10,7071 and upper 13.7567 . This means there is difference between pretest  and posttest by using contextual teaching and learning  (CTL) approach.Thereby, it can be concluded that there is improvement in learning outcomes of basketball dribbling about 1.57% from before and after treatment of contextual teaching and learning (TCL) learning. Keywords: approach, contextual teaching and learning, dribbling, student